Comparative Analysis of Mandarin and Indonesian Consonants - Muhammad Jawad; Karina Fefi Laksana Sakti (Nexus Publishing NXP, 2025)
This study presents a comparative analysis of consonant systems in Mandarin and Indonesian, employing a descriptive-comparative approach. Data were collected through a theoretical literature review, focusing on consonant classification by place and manner of articulation, voicing, and phonotactic distribution. The results reveal that while both languages share similarities in bilabial, alveolar, and velar consonants, as well as stop, fricative, and nasal articulations, their differences are more pronounced. Mandarin exhibits unique features such as phonemic aspiration contrasts, retroflex consonants (/zh/, /ch/, /sh/), and alveopalatal sounds (/j/, /q/, /x/), which are absent in Indonesian. Conversely, Indonesian permits a more flexible coda system (/p/, /t/, /k/, /m/, /n/, /ŋ/, /r/, /l/) compared to Mandarin, which only allows /n/ and /ŋ/. The analysis highlights learning challenges, particularly for Indonesian speakers mastering Mandarin’s aspirated and retroflex consonants. These findings carry pedagogical implications for language instruction, speech therapy, and second language acquisition, emphasizing the need for targeted pronunciation training. This research contributes to phonological typology and offers practical insights for applied linguistics. Keywords: consonants, phonology, comparative, Mandarin, Indonesian